The Effect of Flexible Working Arrangements with Inter-role Conflict on Voluntary Turnover in the Freight Forwarding Industry - Salehati, Nurun Ala; Rojuaniah, Rojuaniah (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2022)
Changes in the way of working have begun to occur along with changes in the environment. This study aims to see the direct effect of flexible work arrangements in terms of flexibility of place and time with conflict between roles such asWork-Home and Home-Work Conflict and to see the moderating effect of strong ties to work (on the job embeddedness) and strong ties outside of work oroff the job embeddednessto voluntary turnover during the pandemic. This research was conducted through the distribution of questionnaires in October to December 2021 to 200 employees of the foreign-owned Transportation Management Services Industry assigned to the administration, finance, marketing and human resources departments operating in Indonesia. Structural Equation Model (SEM) with SmartPLS was used to analyze the data obtained. The results of the study show that flexible working arrangements has almost the same negative effect on Home-Work Conflict and Work-Home Conflict. And both conflicts have a positive effect on Voluntary Turnover with a greater positive influence on Home-Work Conflict and on the moderation of On and Off The Job Embeddedness found only in the moderating effect of Off The Job Embeddedness which moderates the positive influence between Home-Work Conflict and Voluntary Turnover..